Exosomes and exosomal miRNAs: A new therapy for intervertebral disc degeneration - Li, Zhichao; Wu, Yan; Tan, Guoqing; Xu, Zhanwang; Xue, Haipeng (Frontiers in Pharmacology, 2022)
Low back pain has been found as a major cause of global disease burden and disability. Intervertebral disc degeneration is recognized as the vital factor causing low back pain. Intervertebral disc degeneration has a complex mechanism and cannot be avoided. Traditional strategies for the treatment of intervertebral disc degeneration cannot meet the needs of intervertebral disc regeneration, so novel treatment methods are urgently required. Exosomes refer to extracellular vesicles that can be released by most cells, and play major roles in intercellular material transport and information transmission. MicroRNAs have been identified as essential components in exosomes, which can be selectively ingested by exosomes and delivered to receptor cells for the regulation of the physiological activities and functions of receptor cells. Existing studies have progressively focused on the role of exosomes and exosomal microRNAs in the treatment of intervertebral disc degeneration. The focus on this paper is placed on the changes of microenvironment during intervertebral disc degeneration and the biogenesis and mechanism of action of exosomes and exosomal microRNAs. The research results and deficiencies of exosomes and exosomal microRNAs in the regulation of apoptosis, extracellular matrix homeostasis, inflammatory response, oxidative stress, and angiogenesis in intervertebral disc degeneration are primarily investigated. The aim of this paper is to identify the latest research results, potential applications and challenges of this emerging treatment strategy.